RESEPSI MAHASISWA TERHADAP NILAI MORAL TOKOH UTAMA DALAM NOVEL â€œAYAT-AYAT CINTA 1â€ KARYA HABIBURRHMAN EL SHIRAZY - Wulandari Nur Fajriyah; Rasyid Yumna; Nuruddin Nuruddin (Universitas Ahmad Dahlan, 2018)
The objective of this study was to find and to obtain a profound uderstanding of the moral value of the main character in the novel â€œAyat-ayat Cinta 1â€ by Habiburrahman El Shirazy in response the sixth semester students Department of PBSI (Indonesian Language and Literature Education) UIN Syarif Hidayatullah Jakarta. Studentâ€™s receptions include: 1) studentâ€™s response on religious moral values, 2) student response on the moral values of personality, 3) studentâ€™s response on social moral values. This qualitative research was obtained through closed questionnaires and interviews. The data collection procedure is done by determining the respondents who have read and understand the novel, spread the questionnaire, and then do the interview, collecting the data, classify data, and analyze the data. Analytical techniques of data analysis include: the stage of reduction / codification of the data presentation stage, and the stage of conclusion or verification. The result of the research shows that the moral value of religion the main character with percentage 9,3% both, as well as the moral values of personality with percentage 9,0%, and the social moral value with percentage 9,6%. The moral value of the main character can be an example for the student so as to form a strong character in religious moral values, moral values of personality, and social moral values.